2021
DOI: 10.1140/epjc/s10052-021-09213-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing thermal fluctuations through scalar test particles

Abstract: The fundamental vacuum state of quantum fields, related to Minkowski space, produces divergent fluctuations that must be suppressed in order to bring reality to the description of physical systems. As a consequence, negative vacuum expectation values of classically positive-defined quantities can appear. This has been addressed in the literature as subvacuum phenomenon. Here it is investigated how a scalar charged test particle is affected by the vacuum fluctuations of a massive scalar field in D + 1 spacetime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…In Ref. [11] it was shown that this is so because the fluctuations of the gas of photons have anti-correlations, which, when integrated over an infinite interaction time, amount to a finite positive contribution. These anti-correlations arise because, contrarily to the usual thermal case, the field does not only push, but also pulls the dipole.…”
Section: Final Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [11] it was shown that this is so because the fluctuations of the gas of photons have anti-correlations, which, when integrated over an infinite interaction time, amount to a finite positive contribution. These anti-correlations arise because, contrarily to the usual thermal case, the field does not only push, but also pulls the dipole.…”
Section: Final Remarksmentioning
confidence: 99%
“…Moreover, of particular importance for the present work is the notion of subvacuum phenomena [10], for which classically positive quantities assume negative values after renormalization. It was recently shown [11] that temperature can enhance subvacuum effects in some systems of boundary physics. Yet, the possibility of detection requires the thermal fluctuations to be well-known and distinguished from the boundary contributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stochastic motion performed by a point particle when interacting with the quantum vacuum fluctuations of a relativistic field, e.g., scalar or electromagnetic, is also known as Quantum Brownian motion (QBM). This is an example of a phenomena class which arise from quantum vacuum fluctuations and that, over the past several years, has been studied in different scenarios and with different approaches [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The quantum vacuum fluctuations are always present but only become observable when the vacuum is somehow perturbed, for instance, by considering elements such as boundary conditions, temperature, nontrivial topology and so on.…”
Section: Introductionmentioning
confidence: 99%
“…So, negative values for the dispersions in the classical scenario does not make sense. On the other hand, in the quantum context it is possible that (∆A) 2 < 0, which can be interpreted as due to quantum uncertainty reduction [2,3], subvacuum effects [11][12][13] and failure in the renormalization process as a consequence of boundary conditions imposed on the field [10].…”
Section: Introductionmentioning
confidence: 99%